Quality of Life After Myocardial Infarction as a Function of Temperamental Traits, Stress Coping Styles, and Posttraumatic Stress Disorder Symptoms - Burnos, Agnieszka; Wrzosek, Maria (Frontiers in Psychiatry, 2022)
The aim of presented study is to explore the relationship between quality of life after myocardial infarction and factors: temperament, stress coping and PTSD symptoms. Ninety six participants, including 51 females and 45 males aged 24-85, who have survived ST-Elevation Myocardial Infarction were asked to complete Formal Characteristics of Behaviour – Temperament Inventory (FCB-TI), Coping Inventory for Stressful Situations (CISS), PTSD Inventory (PTSD-C) and Quality of life SF-36 questionnaire. According to the obtained results, lower level of briskness and sensory sensitivity, as well as higher level of perseverance and endurance correlate with higher level of emotion-oriented coping, whereas higher level of perseverance, endurance and activity correlates with higher level of avoidant-distracted coping. Moreover, higher level of briskness and activity is correlated with higher level of avoidant-social coping. Higher level of emotion-oriented and avoidant- distracted coping is, in turn, associated with a higher intensity of PTSD symptoms while higher level of avoidant-social coping correlates with lower intensity of PTSD symptoms. Furthermore, higher level of avoidant-distracted coping is correlated to a better physical quality of life, whilst the higher levels of endurance and activity is associated with a better emotional quality of life. Also, the more severe the PTSD symptoms, the lower quality of life in general. Contrastingly, higher sensory sensitivity and briskness correlate with better quality of life. The meaning of other temperamental traits, however, is more ambiguous. Nevertheless, the findings support the model of psychological processes in which the subsequent stages are: temperament – coping– PTSD – quality of life.